COVID-19 and the Digitalisation of Cardiovascular Training and Education—A Review of Guiding Themes for Equitable and Effective Post-graduate Telelearning - Chong, Jun Hua; Chahal, C. Anwar A.; Gupta, Ajay; Ricci, Fabrizio; Westwood, Mark; Pugliese, Francesca; Petersen, Steffen E.; Khanji, Mohammed Y. (Frontiers in Cardiovascular Medicine, 2021)
The coronavirus disease-2019 (COVID-19) pandemic has had an unprecedented impact leading to novel adaptations in postgraduate medical education for cardiovascular and general internal medicine. Whilst the results of initial community COVID-19 vaccination are awaited, continuation of multimodality teaching and training that incorporates telelearning will have enduring benefit to postgraduate education and will place educational establishments in good stead to nimbly respond in future pandemic-related public health emergencies. With the rise in innovative virtual learning solutions, medical educators will have to leverage technology to develop electronic educational materials and virtual courses that facilitate adult learning. Technology-enabled virtual learning is thus a timely progression of hybrid classroom initiatives that are already adopted to varying degrees, with a need for faculty to serve as subject matter experts, to host and moderate online discussions, and to provide feedback and overall mentorship. As an extension from existing efforts, simulation-based teaching (SBT) and learning and the use of mixed reality technology should also form a greater core in the cardiovascular medicine curriculum. We highlight five foundational themes for building a successful e-learning model in cardiovascular and general postgraduate medical training: 1. digital solutions and associated infrastructure; 2. equity in access; 3. participant engagement; 4. diversity and inclusion; and 5. patient confidentiality and governance framework. With digitalisation impacting our everyday lives and now how we teach and train in medicine, these five guiding principles provide a cognitive scaffold for careful consideration of the required ecosystem in which cardiovascular and general postgraduate medical education can effectively operate. With due consideration of various e-learning options and associated infrastructure needs; and adoption of strategies for participant engagement under sound and just governance, virtual training in medicine can be effective, inclusive and equitable through the COVID-19 era and beyond.